2014
DOI: 10.1007/s00424-013-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

Gating modulation by heat of the polycystin transient receptor potential channel PKD2L1 (TRPP3)

Abstract: Polycystic kidney disease 2-like 1 (PKD2L1), previously called transient receptor potential polycystin 3 (TRPP3), forms a voltage-dependent nonselective cation channel that exhibits large tail currents triggered by repolarization after depolarization. Since it has previously been proposed that temperature sensitivity of some TRP channels is linked to the voltage-dependent gating, we here investigated heating effects on PKD2L1 currents in human embryonic kidney HEK293T cells overexpressing mouse PKD2L1. Tail PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…We next examined the temperature sensitivity of the PKD2L1 channel. As previously reported [6], although heating to 40°C increased and decreased a single-channel conductance and channel activity (NPo) of the WT channels, respectively (data not shown), rapid decrease in the temperature induced an obvious activation of the WT channels (Fig. 5A).…”
Section: The Outer Pore Loop Region Of the Mouse Pkd2l1 Channel Regulsupporting
confidence: 86%
“…We next examined the temperature sensitivity of the PKD2L1 channel. As previously reported [6], although heating to 40°C increased and decreased a single-channel conductance and channel activity (NPo) of the WT channels, respectively (data not shown), rapid decrease in the temperature induced an obvious activation of the WT channels (Fig. 5A).…”
Section: The Outer Pore Loop Region Of the Mouse Pkd2l1 Channel Regulsupporting
confidence: 86%
“…Thus, we conducted single-channel recordings and observed an increase in the unitary single-channel conductance (163 to 209 pS), consistent with reports using the mouse ortholog of TRPP2 (SI Appendix, Fig. S6D) (40). Since ion conductance is a property of the channel pore and not the voltage sensor, we tested if the TRPP2 channel can be gated independently of a functioning voltage sensor.…”
Section: Gating Charge Transfer Is Required To Polymodally Activate Tsupporting
confidence: 83%
“…Besides osmotic membrane swell, heat is another stimulus that polymodally potentiates polycystin channel currents. Currents carried by homomeric TRPP2 and heteromeric TRPP2+PKD1-L1 channels are potentiated by heat when expressed in the cilium (temperature coefficient Q 10 = 8) and plasma membranes (Q 10 = 6) (24,40). We wondered if heat might alter TRPP2 voltage-dependent gating as a mechanism for the observed effect.…”
Section: Gating Charge Transfer Is Required To Polymodally Activate Tmentioning
confidence: 99%
“…More recently, careful biophysical experiments have shown that PK32L1, also known as TRPP3, can form homomeric channels; these channels are activated by high voltages, giving rise to large tail currents measured on repolarization (30). Homomeric PKD32L1 channels are sensitive to temperature (31), and osmotic pressure (30) and show a bimodal sensitivity to pH (32). PKD2L1 has also been proposed to mediate calcium entry into the primary cilium, where it regulates developmental patterning (33).…”
Section: Discussionmentioning
confidence: 99%